2011
DOI: 10.1292/jvms.10-0381
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ovarian Status and Follicular Diameter on Maturational Ability of Domestic Cat Oocytes

Abstract: ABSTRACT. The objective of this study was to clarify the effect of ovarian status and follicular size on morphological normality and maturational ability of cat oocytes. Ovarian status was classified into inactive, follicular, luteal and prepubertal, and follicles were classified into three groups according to their diameter (400-800, 800-1200 and 1200-2000 µm). In each ovarian status, the number of follicles decreased but the percentage of morphologically normal oocytes increased with the growth of follicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…(166.2 ± 2.6 μm) in the dromedary camel (Abdoon et al., ). We found that the size of the vesicular follicle did not affect the oocyte diameter (data not shown), which disagrees with the cat (another induced ovulation mammals) (Uchikurai, Nagano, & Hishinuma, ). The diameter of the mammalian oocyte plays an essential role in the resumption of meiotic division; it is well known that oocytes with diameters of 100–110 μm gradually achieve competence to resume meiotic division.…”
Section: Discussioncontrasting
confidence: 78%
“…(166.2 ± 2.6 μm) in the dromedary camel (Abdoon et al., ). We found that the size of the vesicular follicle did not affect the oocyte diameter (data not shown), which disagrees with the cat (another induced ovulation mammals) (Uchikurai, Nagano, & Hishinuma, ). The diameter of the mammalian oocyte plays an essential role in the resumption of meiotic division; it is well known that oocytes with diameters of 100–110 μm gradually achieve competence to resume meiotic division.…”
Section: Discussioncontrasting
confidence: 78%
“…() and Otoi, Murakami, Ooka, Karja, and Suzuki (). A possible explanation for these highly variable maturation rates is that the ovaries that have been used came from young and old, fat or anorectic, pregnant or pre‐pubertal cats, cats in heat or in anoestrus; all these parameters can affect the maturation rate of the obtained oocytes (Martins, Fernandes, Landim‐Alvarenga, & Lopes, ; Martins, Fernandes, Minto, Landim‐Alvarenga, & Lopes, ; Uchikura, Nagano, & Hishinuma, , ). A study from Uchikura et al.…”
Section: Introductionmentioning
confidence: 99%
“…Since the estrous stage of the queens was not considered in this study, the differences in the results for Grade 3 oocytes among the experiments may have been due to the use of oocytes at different stages of the estrous cycle. Moreover, another group [26] has suggested that the size of the follicles/oocytes, as well as their qualities, may affect the in vitro maturation and subsequent development of cat oocytes. Therefore, future studies should evaluate the effects of the stage of the estrous cycle, as well as oocyte diameter, on the development of Grade 3 oocytes.…”
Section: Discussionmentioning
confidence: 99%